ENVIRONMENTAL IMPACTS OF SPORTS TOURISM: A CASE STUDY OF OVERCROWDING, POLLUTION AND WASTE MANAGEMENT DURING 2023 AFCON (Academicia Globe: Inderscience Research, 2025)
This paper investigated the environmental impacts of sports tourism: A case study of overcrowding, pollution and waste management during 2023 AFCON. The research design adopted for this study is descriptive and survey-based, which enabled the systematic collection of primary data through the administration of a structured questionnaire. The study focused on a sample of 150 respondents, selected from various communities within the Local Government Area. Descriptive analysis was employed to analysis the data. Result from the study revealed that There will be percentage increase in tourist influx during the hosting of AFCON competitions. The percentage increase in tourist influx will lead environmental pollution during the hosting of AFCON competitions. Increased waste generation and poor waste management will be the major sources of environmental pollution during the hosting of AFCON competitions. High-level traffic congestion and air pollution from vehicular emissions will be the major sources of environmental pollution during the hosting of AFCON competitions. Overcrowding of tourist destinations and natural reserve will be the major sources of environmental pollution during the hosting of AFCON competitions.